CHALLENGES FACING MODERN MECHANICAL ENGINEERING APPLICATIONS IN THE CONTEXT OF INDUSTRY 4.0: CHALLENGES FACING MODERN MECHANICAL ENGINEERING APPLICATIONS IN THE CONTEXT OF INDUSTRY 4.0 - Antonova, Mariela; Antonov, Stamen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The article explores the challenges and opportunities facing modern mechanical engineering applications in the era of Industry 4.0. It analyzes the integration of cyber-physical systems, the Internet of Things (IoT), artificial intelligence (AI), and additive manufacturing into the traditional production environment. Emphasis is placed on digital transformation, automation, and smart factory concepts, which redefine design, production, and maintenance processes. The paper also addresses human and organizational challenges, such as workforce upskilling, digital culture, and interdisciplinary collaboration. The discussion concludes with an outlook on Industry 5.0, focusing on human-centered innovation and sustainable manufacturing.